Modern weapons and military equipment for issue 2-2015 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Weapons "FN P-90"The emergence and development of the concept of weapons for personal protection. A detailed description of the structural design of Belgian weapons "FN P-90", with emphasis on experiences from field use, and tactical - technical data.